Clinical and dermoscopic features of eruptive collagenomas localized only on the neck in a young female - Satyendra Kumar Singh; Vandana Yadav; Chandra Pratap Singh; Atul Mohan (Wolters Kluwer Medknow Publications, 2023)
Eruptive collagenomas are rare nonfamilial connective tissue nevi of unknown etiology and pathogenesis, which are characterized by an abrupt onset of asymptomatic papules, nodules, and plaques on the trunk and extremities. Herein, we report a unique case of eruptive collagenoma in a 29-year-old female, who presented with multiple asymptomatic skin-colored to slightly hyperpigmented papules over the anterolateral aspect of the neck with no systemic involvement. Family history was unremarkable, and the diagnosis was confirmed by histopathological examination which showed thickened homogenized collagen bundles in the superficial dermis. We report this case due to the paucity of cases in Indian literature on eruptive collagenoma in a young female with only neck involvement.